TRAFO OIL FAILURE BASED ON DISSOLVED GAS ANALYSIS AND VOLTAGE BREAKDOWN RESULTS - Fauji, Ahmad; Kurnianto, Rudi; Rajagukguk, Managam (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2023)
Contamination on the transformer oil can lead to the oil failure of the transformator. Therefore, the transformer oil needs to be tested to make sure the oil is still in good condition. To find indications of oil failure the transformator needs to be tested DGA and BDV. From the results of the analysis with the TDCG method, the gas content in the transformer oil is less than 720 ppm so according to the IEEE standard, the oil transformer is indicated in normal conditions. In the Key Gas method, the percentage of the dominant carbon monoxide gas content is in the range of 85-90% so it is indicated that heating occurs on paper insulation. In the Duval Triangle method, the cut point between methane gas, ethylene and acetylene is in zone 1 and zone 2 so indicated that the oil of the transformator has thermal interference. In the BDV test, the transformer oil resistance values of 40.43 kV and 38.98 kV were obtained according to the IEC oil standard indicated in normal conditions. Of the four methods used to analyze the condition of the oil transformers concluded the oil of the transformers in a good condition but indicated heating.